Fine-tuning germline mutation rates across evolution - Bush, SJ; Goriely, A (Cell Press, 2023)
The germline mutation rate (GMR) sets the pace at which mutations, the raw material of evolution, are introduced into the genome. By sequencing a dataset of unprecedently broad phylogenetic scope, Bergeron et al. estimated species-specific GMR, offering numerous insights into how this parameter shapes and is shaped by life-history traits.